Influência da infecção pelo vírus da artrite-encefalite caprina nos perfis soro-epidemiológicos em caprinos infectados pelo Toxoplasma gondii e Neospora caninum - Stachissini, Anee Valéria Mendonça [UNESP] (2005)
With the aim of evaluating the seroepidemiological profiles of the toxoplasmosis and neosporosis in dairy goats from Sao Paulo state; possible risks of the toxoplasmosis for the public health and the associations of the diseases with the co-infection by the caprine arthritis-encephalitis virus (CAEV); and to stablish a quantitative indicator of the health (L°sanitary statusLl) of the farms, 923 caprine serum samples were obtained from 17 different properties. The animals were male and female , over three months old, subdivided in three age groups: < 1 year-old, between 1 and 4 years-old and > 4 years-old. For toxoplasmosis, neosporosis and caprine arthritis-encephalitis diagnosis, were used, respectively, indirect immunofluorescent antibody test (IFATLÃ16), Neospora agglutination test (NATLÃ25) and agar gel immunodiffusion (IDGA, positive or negative). A questionnaire containing reproductive and epidemiologic information was applied for all the farms. All the discussion were realized at 5% significance level. The positivity rates were 23.40 % for the toxoplasmosis and 19.77 % for the neosporosis. Two properties presented no positive result for T. gondii and in one there was no seropositive animal for N. caninum. There were no associations between the frequency of seropositivity and sex for both diseases. A more advanced age influenced positively in the occurrence of anti-T. gondii antibodies, but there no statistical difference for N. caninum. The presence of cats and dogs in farms was associated to the raise of positive rates for toxoplasmosis and neosporosis, respectively. The seropositivity for just one of the agents (T. gondii or N. caninum) did not influence the ocurrence of reproductive failures. There was no association between anti-CAEV antibodies and the presence of antibodies anti-T. gondii or anti-N. caninum... (Complete abstract, click electronic access below)